2010
DOI: 10.1007/s10164-010-0231-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in calling effort in the bell cricket Meloimorpha japonica

Abstract: We investigated how male age and body weight influence male mating effort in the bell cricket Meloimorpha japonica. We adopted a longitudinal approach to study resource allocation to male mating effort (calling duration during 24 h) in the bell cricket. Calling durations and body weight of each male were measured at 7-8 days (young age), 14-15 days (middle age), and 22-25 days (old age) after the final molt. Calling duration increased between young and middle age. During the period between middle and old age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Mountjoy & Lemon 1995; Cote et al. 2010; Lafaille, Bimbard & Greenfield 2010; Kuriwada & Kasuya 2011) and may represent terminal investment in some cases. Facultative increases in signalling by males experiencing an acute survival threat also imply terminal investment; putative examples include the augmented courtship activity of male Drosophila nigrospiracula parasitized by mites (Polak & Starmer 1998) and the heightened aggression and attractiveness of male Peromyscus leucopus mice harbouring botflies (Cramer & Cameron 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mountjoy & Lemon 1995; Cote et al. 2010; Lafaille, Bimbard & Greenfield 2010; Kuriwada & Kasuya 2011) and may represent terminal investment in some cases. Facultative increases in signalling by males experiencing an acute survival threat also imply terminal investment; putative examples include the augmented courtship activity of male Drosophila nigrospiracula parasitized by mites (Polak & Starmer 1998) and the heightened aggression and attractiveness of male Peromyscus leucopus mice harbouring botflies (Cramer & Cameron 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, younger males pay greater costs than older ones when they are killed or injured (Williams, 1966; Charlesworth & Leon, 1976; Clutton‐Brock, 1984). Most studies on life‐history theory focus on quantifiable aspects of mating behaviour such as female reproductive investment and male courtship signals (Poizat et al , 1999; Kemp, 2002; Hunt et al , 2004; Kuriwada & Kasuya, 2006, 2011; Judge et al , 2008). Less quantifiable factors, such as anti‐predatory behaviours, have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Tel. : +81 98 886 3880; e-mail: t.kuriwada@gmail.com as female reproductive investment and male courtship signals (Poizat et al, 1999;Kemp, 2002;Hunt et al, 2004;Kuriwada & Kasuya, 2006, 2011Judge et al, 2008). Less quantifiable factors, such as anti-predatory behaviours, have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in signaling as courters aged was observed in Meloimorpha japonica (bell cricket). This finding is similar to Bertram et al's (2021) findings on G. assimilis, as they found that the degree of change in time spent calling was positively correlated with courter body weight, indicating that older and better-quality males were better able to invest more resources into mating than younger or poor-quality males (Kuriwada & Kasuya, 2011). However, some studies suggest that older courters decrease the energetic investment in their mate attraction signals, as their syllable duration, calling bout duration and amplitude decrease, while the silent portions in their calls simultaneously increase in duration (Verburgt et al, 2011).…”
Section: Chapter 1 -How Acoustic Mate Attraction Signaling Is Influen...supporting
confidence: 86%